2007
DOI: 10.1002/ca.20574
|View full text |Cite
|
Sign up to set email alerts
|

The clinical anatomy of congenital portosystemic venous shunts

Abstract: Congenital portosystemic venous shunts are rare. Their gross anatomy has not been well defined. Four different varieties of congenital portosystemic venous shunts are described in six children seen during a 10-year period, focusing on the anatomy of the shunt as determined by imaging studies and surgery. A detailed review of the literature indicates that congenital portosystemic venous shunts are best classified as: extrahepatic or intrahepatic. Extrahepatic shunts may be further subdivided into portocaval shu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
183
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 159 publications
(186 citation statements)
references
References 50 publications
2
183
0
1
Order By: Relevance
“…Various imaging modalities and blood tests indicated that the natural histories of intrahepatic and extrahepatic CPSSs differed. Intrahepatic CPSS without hepatic tumor has been reported to spontaneously close or regress, whereas extrahepatic CPSS does not spontaneously regress (3,7,8,(16)(17)(18). Ultrasonography and dynamic contrast-enhanced CT evaluation showed spontaneous reductions in the shunt size in all of our patients with intrahepatic CPSS but in none with extrahepatic CPSS, strengthening the previous findings.…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…Various imaging modalities and blood tests indicated that the natural histories of intrahepatic and extrahepatic CPSSs differed. Intrahepatic CPSS without hepatic tumor has been reported to spontaneously close or regress, whereas extrahepatic CPSS does not spontaneously regress (3,7,8,(16)(17)(18). Ultrasonography and dynamic contrast-enhanced CT evaluation showed spontaneous reductions in the shunt size in all of our patients with intrahepatic CPSS but in none with extrahepatic CPSS, strengthening the previous findings.…”
Section: Discussionsupporting
confidence: 86%
“…Surgical repair or embolization may be recommended for extrahepatic CPSS without closure because of the high risk of hepatopulmonary syndrome, pulmonary hypertension, and hepatic encephalopathy (4,7,8,(13)(14)(15)(16). Stringer (8) described that CPSS-affected individuals are at risk of developing hepatic encephalopathy and/or an intrahepatic tumor depending largely on the volume and duration of the shunt.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations